2015
DOI: 10.1002/sam.11265
|View full text |Cite
|
Sign up to set email alerts
|

It takes two to tango: Exploring social tie development with both online and offline interactions

Abstract: Understanding social tie development among users is crucial for user engagement in social networking services. In this paper, we analyze the social interactions, both online and offline, of users and investigate the development of their social ties using data trail of 'how social ties grow' left in mobile and social networking services. To the best of our knowledge, this is the first research attempt on studying social tie development by considering both online and offline interactions in a heterogeneous yet r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Understanding social bonds development among users is essential for user participation in co-creation online (Yin et al , 2015). One of the marketers said:…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Understanding social bonds development among users is essential for user participation in co-creation online (Yin et al , 2015). One of the marketers said:…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Yin et al later extended the work by investigating the tie between offline and online interactions, and found that the collective level of online interaction is independent with offline interaction. However, mutual friends' activities (that can be observed online) may play a significant role in inducing offline activities [43]. These works illustrate initial steps towards studying offline-online interactions in event-based social media networks.…”
Section: Offline-online Interactionsmentioning
confidence: 84%
“…Multiple studies have found close ties between offline and online worlds, allowing interactions in the social networks to reflect those of the real world [23,43]. If such an assumption holds, one could predict whether a person is being sick just by observing his/her social network activities.…”
Section: Introductionmentioning
confidence: 99%
“…First, based on the entire physical locations and held time of all the events in our data sets, we get 30 regions and 21-time slots. In particular, the 30 ) denotes whether user u has attended events held in region r (or on time slot t). Third, using MF technique, we factorize matrix MT into two matrices UT θ θ = ,…,…”
Section: User Preference and Item Attribute Computationmentioning
confidence: 99%